THE LESSON OF THE RUSSIAN LANGUAGE AS A FOREIGN LANGUAGE (Archive of Conferences, 2020)
A lesson is the main organizational unit of the educational process; the purpose of the lesson is to achieve a completed but intermediate learning goal. As a rule, the lesson is conducted with a permanent composition of students and is based on the training program. A system of lessons means a series of practical exercises united by a single theme or goal. The lesson of Russian as a non-native language – along with the practical goal-implements. In this article explains the the main features of the lesson Russian language and teaching it to bilingual children